Utilization of coal fly ash waste for effective recapture of phosphorus from waters. (January 2022) - Xu, Rui; Lyu, Tao; Wang, Lijing; Yuan, Yuting; Zhang, Meiyi; Cooper, Mick; Mortimer, Robert J.G.; Yang, Queping; Pan, Gang
Abstract: Reutilization of the waste by-products from industrial and agricultural activities is crucially important towards attainment of environmental sustainability and the 'circular economy'. In this study, we have developed and evaluated a sustainably-sourced adsorbent from coal fly ash, which was modified by a small amount of lanthanum (La-FA), for the recapture of phosphorous (P) from both synthetic and real natural waters. The prepared La-FA adsorbent possessed typical characteristic diffraction peaks similar to zeolite type Na–P1, and the BET surface area of La-FA was measured to be 10.9 times higher than that of the original FA. Investigation of P adsorption capability indicated that the maximum adsorption (10.8 mg P g −1 ) was 6.14 times higher than that (1.8 mg P g −1 ) of the original fly ash material. The ζ potentials measurement and P K-edge X-ray Absorption Near Edge Structure (XANES) spectra demonstrated that P was bonded on La-FA surfaces via an adsorption mechanism. After applying the proposed adsorbent to real lake water with La/P molar ratios in the range from 0.5:1 to 3:1, the La-FA adsorbent showed the highest phosphate removal ability with a La/P molar ratio 1:1, and the P adsorption was similar to that performance with the synthetic solution. Moreover, the La-FA absorbent produced a negligible effect on the concentrations of total dissolved nitrogen (TDN), NH4 + -N and NO3 − -N in water. This study thus provides a potential material for effective P recapture and details of its operation. Graphical abstract: Image 1 Highlights: Lanthanum modified fly ash (La-FA) was proven to act as a sustainable-sourced P absorbent. La-FA showed 6 times higher P adsorption ability compared with the original material. P removal performance from natural water was similar to that of synthetic solution. Surface P adsorption was deemed the main mechanism via XANES spectral analyses.